1997
DOI: 10.1101/gr.7.11.1061
|View full text |Cite
|
Sign up to set email alerts
|

AluInsertion Polymorphisms and Human Evolution: Evidence for a Larger Population Size in Africa

Abstract: Alu insertion polymorphisms (polymorphisms consisting of the presence/absence of an Alu element at a particular chromosomal location) offer several advantages over other nuclear DNA polymorphisms for human evolution studies. First, they are typed by rapid, simple, PCR-based assays; second, they are stable polymorphisms-newly inserted Alu elements rarely undergo deletion; third, the presence of an Alu element represents identity by descent-the probability that different Alu elements would independently insert i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
247
3
5

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(281 citation statements)
references
References 40 publications
(67 reference statements)
26
247
3
5
Order By: Relevance
“…Saab et al (2004) have typed the ACE I/D gene polymorphism in the Lebanese population, where the homozygous II genotype accounted for 8 % of the sample -an incidence that was found to be atypically low relative to European and East Asian populations. These preliminary results suggested that the ACE II genotype frequency might vary according to a geographic trend, as has been postulated for other Alu insertion polymorphisms (Stoneking et al, 1997). The objective of the present study was to determine whether the ACE I/D gene polymorphism frequency did indeed correlate with geographic distance and then identify whether the ACE gene can be considered as a genetic marker for the past demography of human populations.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Saab et al (2004) have typed the ACE I/D gene polymorphism in the Lebanese population, where the homozygous II genotype accounted for 8 % of the sample -an incidence that was found to be atypically low relative to European and East Asian populations. These preliminary results suggested that the ACE II genotype frequency might vary according to a geographic trend, as has been postulated for other Alu insertion polymorphisms (Stoneking et al, 1997). The objective of the present study was to determine whether the ACE I/D gene polymorphism frequency did indeed correlate with geographic distance and then identify whether the ACE gene can be considered as a genetic marker for the past demography of human populations.…”
Section: Introductionmentioning
confidence: 61%
“…Broader conclusions, such as identifying the origin of a particular polymorphism on the basis of its relative frequency, are less controversial; and this is more so with Alu elements, which are considered to be highly stable polymorphisms, where deletion of newly inserted elements is a rare event (Stoneking et al, 1997). Low frequencies of the insertion are therefore indicative of the ancestral state, and African populations tend to have not only the lowest frequency of the insertion (Bayoumi et al, 2006) but also the greatest variation in frequency (Stoneking et al, 1997). On this basis it would appear that the ALU deletion within the ACE gene was, of the populations studied here, Middle Eastern in origin.…”
Section: (I) Ace I/d Genotype Distributionmentioning
confidence: 99%
“…Eight human-specific Alu insertion polymorphisms (DM, HS2.43, B65, PV92, D1, F13B, A25 and TPA25) were typed using the primers and polymerase chain reaction (PCR) amplification conditions previously described in Stoneking et al (1997) and Edward and Gibbs (1992), with minor modifications. As for STRs, CD4 consists of a pentanucleotide (TTTTC) n repeat amplified according to Tishkoff et al (1996), with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…These samples (see Fig. 1 for geographical location) come from the works of Stoneking et al (1997), Comas et al (2000) and Garcia-Obregon et al (2006, 2007. The consulted population data from CD4, F13B and DM STRs was obtained from the ALFRED database (Rajeevan et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Low variability in three parameters was obtained in these two groups, compared to the others; and (c) Deka et al (1999) References: 1. Batzer et al (1994); Stoneking et al (1997); Novick et al (1998); 2. Gaedigk et al (1998) Deka et al (1991Deka et al ( , 1994Deka et al ( , 1999, Deka and Chakraborty (1999); Destro-Bistrol et al (2000); 10.…”
Section: Other Autosome Markersmentioning
confidence: 99%